DISTRIBUSI PENDAPATAN PETANI DI DESA KAPATARAN SATU KECAMATAN LEMBEAN TIMUR - Philips H. Karundeng; Eyverson Ruauw; Celsius Talumingan (Universitas Sam Ratulangi, 2015)
ABSTRAC This study aims to determine the distribution of the income of farmers in the village Ka- pataran The District of East Lembean using primary and secondary data, which for secondary data obtained from agencies associated with this research, while primary data was taken at ran- dom by using a list of questions (questionnaire ). Selected Villages Kapataran One who has a number of farmers 60 305 inhabitants of the population of farmers as an area of research, be- cause the village is a small village with a population compared to other villages in the district and village Lembean East is a source of revenue that is homogeneous and the District of East Lembean as one of the agricultural centers in Minahasa, North Sulawesi. The number of farmers who used a sample of 60 farmers or farm households. The degree of inequality of income distri- bution seen from the farm business income only by the Gini index ketimpangannya level being, while based on the World Bank krieria inequality is very lame. Judging from the total income derived from agricultural and non-agricultural businesses inequality of income distribution seen Gini index is also at a moderate level, but based on the World Bank is very lame Inequality nice views of the Gini index and the World Bank criteria with their off-farm businesses increased lev- el ketimpangannya. With the jobs that are open to the public so that more utilize income is so high that its income distribution is more increased when in tambahakan with non-agricultural businesses.Â Â Keywords: farmers income